2014
DOI: 10.1111/jai.12442
|View full text |Cite
|
Sign up to set email alerts
|

Helminth communities of the Turkish endemic fish, Pseudophoxinus crassus (Ladiges, 1960): four helminth parasites for a new host record

Abstract: Summary Tuz Gölü (Salt Lake) Basin is one of the largest hypersaline lakes in the world and of extremely high biological importance owing to its high diversity and high level of endemism. It is hypothesized that the basin environment and the endemism of Pseudophoxinus crassus – a species of ray‐finned fish in the Cyprinidae family and found only in Turkey – might contribute to the host‐specific parasite characters. A total of 92 P. crassus specimens were collected by electrofishing between spring 2009 and autu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In contrast, other studies have revealed the relationship between parasite infection and the sex of the fish host. For example, some studies have found that relationship in acanthocephalans, e.g., Aydogdu, Erk'akan, Keskin, Innal, and Aslan () in Pomphorhynchus laevi s infecting the fat spring minnow Pseudophoxinus crassus from the Incesu stream, Aydogdu, Emre, & Emre () for Neoechinorhynchus agilis in the thicklip grey mullet Chelon labrosus from the Beymelek Lagoon, and Aydogdu, Keskin, Erk'akan, & Innal, () for P. laevis in the Beysehir dace Squalius anatolicus from the Sarısu stream. In all these studies, authors found that parasite infection levels were higher in male hosts than in females.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other studies have revealed the relationship between parasite infection and the sex of the fish host. For example, some studies have found that relationship in acanthocephalans, e.g., Aydogdu, Erk'akan, Keskin, Innal, and Aslan () in Pomphorhynchus laevi s infecting the fat spring minnow Pseudophoxinus crassus from the Incesu stream, Aydogdu, Emre, & Emre () for Neoechinorhynchus agilis in the thicklip grey mullet Chelon labrosus from the Beymelek Lagoon, and Aydogdu, Keskin, Erk'akan, & Innal, () for P. laevis in the Beysehir dace Squalius anatolicus from the Sarısu stream. In all these studies, authors found that parasite infection levels were higher in male hosts than in females.…”
Section: Discussionmentioning
confidence: 99%
“…larvae attached in the abdominal cavity of Pseudophoxinus battalgilae that lived in Antalya Bay with a total prevalence 47.6 %. Aydoğdu et al (2014) conducted a study in İncesu Stream -Konya Province and four parasitic helminth species were detected; Asymphylodora imitans (28.2 %), Bothriocephalus acheilognathi (1.08 %) and Pomphorhynchus laevis (52.1 %) in the intestines of Pseudophoxinus crassus while Gyrodactylus latus (5.4 %) in the gills of host fishes. The study was carried out in Düger Creek by Innal et al (2017) and Lernaea cyprinacea were found in P. burduricus overall prevalence (28.3 %) as mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the prevalence of different kinds of parasites was examined, revealing intriguing patterns. It was described that the parasites Pomphorhynchus laevis and Gyrodactylus latus significantly affect males, whereas the parasitic infection caused by Asymphylodora immitans had a prevalence in females within the same fish (Aydogdu et al, 2014).…”
Section: Parasitic Infectionsmentioning
confidence: 99%